KOMUNIKASI PEMASARAN PARIWISATA DAN KUNJUNGAN WISATAWAN DI BANGKALAN - Linasari, Festi; Sumarah, Noorshanti; Andayani, Sri (Universitas 17 Agustus 1945 Surabaya, 2016)
This research based on tourism which has become an important asset for Kabupaten Bangkalanand needed to be informed to the people. The ministry of Youth, Sport, Culture and TourismKabupaten Bangkalan is a government institution which work on tourism and the job is to promote theexisting tourism. This research is aiming to describe Marketing Communication which has been doneby The ministry of Youth, Sport, Culture and Tourism Kabupaten Bangkalan on increasing the touristvisit. The focuses in this research are Siring Kemuning Beach, Guweh Pote Jaddih Hills andSwimming pool, And Pesarean Syaikhona Kholil. The teory used in this research is IntegratedCommunication Marketing (IMC). The research method which is used in this research is Qualitativewith desciptive type. The result from the research found that Marketing Communication activity byThe ministry of Youth, Sport, Culture and Tourism Kabupaten Bangkalan on increasing the touristvisit used Integrated Marketing Communication such as Advertising, Direct Marketing, InteractiveMarketing, Sales Promotion, Publicity or Public Relations, Personal sales, Events and Experiences,Person to Person, but in reality The ministry of Youth, Sport, Culture and Tourism KabupatenBangkalan has not been maximizing the elements of Integrated Marketing Communication that canincrease the numbers of tourists visit. The researcher also found that tourism object Guweh PoteJaddih Hills and Swimming pool have not under the controll of The ministry of Youth, Sport, Cultureand Tourism Kabupaten Bangkalan and still in private or individual claim, this is so unfortunatebecause this tourism object attaracts many tourists visit.Keywords : communication marketing tourism, increase, tourism visit.